TET Upregulation Leads to 5-Hydroxymethylation Enrichment in Hepatoblastoma - Rivas, Maria Prates; Aguiar, Talita Ferreira Marques; Fernandes, Gustavo Ribeiro; Caires-Júnior, Luiz Carlos; Goulart, Ernesto; Telles-Silva, Kayque Alves; Cypriano, Monica; de Toledo, Silvia Regina Caminada; Rosenberg, Carla; Carraro, Dirce Maria; da Costa, Cecilia Maria Lima; da Cunha, Isabela Werneck; et al. (Frontiers in Genetics, 2019)
Hepatoblastoma is an embryonal liver tumor carrying few genetic alterations. We previously disclosed in hepatoblastomas a genome-wide methylation dysfunction, characterized by hypermethylation at specific CpG islands, in addition to a low-level hypomethylation pattern in non-repetitive intergenic sequences, in comparison to non-tumoral liver tissues, shedding light into a crucial role for epigenetic dysregulation in this type of cancer. To explore the underlying mechanisms possibly related to aberrant epigenetic modifications, we evaluated the expression profile of a set of genes engaged in the epigenetic machinery related to DNA methylation (DNMT1, DNMT3A, DNMT3B, DNMT3L, UHRF1, TET1, TET2 and TET3), as well as the 5-hydroxymethylcytosine (5hmC) global level. We observed in hepatoblastomas a general disrupted expression of these genes from the epigenetic machinery, mainly UHRF1 and TET1 and TET2 upregulation, in association with an enrichment of 5hmC content. Our findings support an active model of demethylation by TETs in hepatoblastoma, probably during early stages of liver development, which in combination with UHRF1 overexpression would lead to DNA hypomethylation and an increase in overall 5hmC content. Furthermore, our data suggest that decreased 5hmC content might be associated with poor survival rate, highlighting a pivotal role of epigenetics in hepatoblastoma development and progression.